Internationalization of Indonesian Islamic Higher Education in the Digital Transformation Era: Opportunities and Challenges (QUALITY, 2025)
This conceptual article examines the internationalization of Islamic universities in Indonesia in the context of digital disruption. Although previous studies have addressed the general topic of higher education internationalization, little attention has been given to how Islamic universities can globalize while maintaining their unique integration of science, religion, and Islamic moderation. Employing a library research method and utilizing a SWOT analysis approach, this study examines relevant laws, ministerial regulations, and policy documents. The findings indicate that Islamic higher education institutions (PTKI) have strategic strengths in integrating science and religion and have a moderate Islamic identity that distinguishes them from other universities worldwide. From an opportunity perspective, PTKIs can leverage digital transformation, international cooperation policies, and the Merdeka Belajar-Kampus Merdeka (MBKM) program to expand their global academic networks. However, the study also revealed fundamental weaknesses: the absence of regulations for the internationalization of PTKIs, dual authority between ministries, and internal limitations in human resources, international publications, infrastructure, and funding. PTKIs also face serious challenges, including the risk of pseudo-internationalization, tension between Islamic identity and secular academic standards, and global competition and geopolitical dynamics that can hinder academic mobility.